Formulation and Characterization of Genistein-loaded Nanostructured Lipid Carriers: Pharmacokinetic, Biodistribution and In vitro Cytotoxicity Studies - MIttal, Pooja; Vrdhan, Harsh; Ajmal, Gufran; Bonde, Gunjan; Kapoor, Ramit; Mishra, Brahmeshwar (Current Drug Delivery, 2019)
Background: Genistein (Gen) is a naturally occurring soy isoflavonoid, possessing anticancer, antiproliferation & antioxidant-like properties. The disadvantage of poor solubility and less oral bioavailability restrict its use as a potential anticancer agent. Objectives: The current work was focused on the formulation and characterization of the genistein loaded nanostructured lipid carriers that can entrap enough quantity of the drug which will provide sustained release of the drug for the treatment of ovarian cancer. Methods: The nanostructure lipid carriers of genistein were developed with the aid of solvent emulsification and evaporation technique by employing TPGS as a surfactant. The resultant formulation was characterized by various physicochemical properties. Pharmacokinetics and biodistribution studies were carried out to estimate the mean plasma concentrations of the drug. Percentage cytotoxicity was evaluated by using PA-1 ovarian cancer cell lines. Results: The resultant formulation exhibited a particle size of 130.23 nm, and entrapment efficiency of 94.27 %, & zeta potential of -20.21 mV with unimodal size distribution. Pharmacokinetics and biodistribution studies revealed that the formulation was able to provide sufficient plasma drug concentration for the longer period of time and the drug was more distributed in ovarian cancer tissues. Results of MTT assay concluded that GenNLC were more effective in comparison to pristine Gen. Conclusion: In a nutshell, GenNLC seems to be a superior alternative carrier system for the formulation industry to obtain the higher entrapment with excellent stability of the formulation.
Keywords: Genistein